Ocean bottom hydrophone sgy-files of wide-angle seismic data of profile ATLANTIS-I, 31ºN Central Atlantic - Grevemeyer, Ingo; Ranero, César R; Ugalde, Arantza; Prada, Manel (PANGAEA, 2024)
Wide-Angle Seismic (WAS) data acquired across ATLANTIS-I profile in 2022 at 31ºN Central Atlantic. The seismic data were recorded with 22 ocean bottom hydrophones (OBH) from GEOMAR (Germany), deployed every ~8 km along the transect. Processing of OBH data involved receiver relocation using an in-house Metropolis-Hasting grid-search algorithm, a Wiener predictive error filtering, and a band pass filter.
Keywords: Atlantic Ocean; OBH; wide-angle seismic